Career issue: effects of sexual harassment towards individuals in workplace - Mun, Yap Choon; Hern, Chong Yi; Wan Othman, Wan Norhayati; Zainudin, Zaida Nor; Anuar, Muharram (Human Resources Management Academic Research Society (HRMARS), 2024)
Sexual harassment remains a critical issue in the workplace, significantly affecting employees' mental health, job satisfaction, and overall organizational culture. This review aimed to systematically explore the psychological, occupational, and organizational consequences of workplace sexual harassment and identify effective prevention and intervention strategies. PRISMA model was used to identify the multifaceted impacts of sexual harassment on individuals and effective prevention strategies. This methodology allowed for a comprehensive synthesis of data across various workplace settings. The review reveals that sexual harassment in the workplace leads to profound psychological distress, including depression, anxiety, and decreased self-esteem. These psychological effects contribute to reduced job satisfaction and increased turnover intentions, resulting in higher employee turnover rates and associated organizational costs. Additionally, the negative effects of harassment extend beyond the workplace, disrupting employees' work-family balance and overall quality of life. Further research is needed to evaluate the long-term effectiveness of various prevention strategies and to develop comprehensive models for assessing the risk factors and impacts of sexual harassment. Effective prevention and intervention strategies are crucial for mitigating the impacts of workplace sexual harassment. By understanding the multifaceted impacts of sexual harassment and implementing robust preventive measures, organizations can foster safer, more inclusive workplaces that enhance employee well-being and productivity.